Effects of mine tailings exposure on early life stages of Atlantic cod - Reinardy, Helena; Pedersen, Kristine Bondo; Nahrgang, Jasmine; Frantzen, Marianne (Environmental Toxicology and Chemistry, 2019)
In Norway, mine tailings waste can be deposited by coastal submarine dispersal. Mine tailings slurry includes fine particles <10 µm with elevated levels of metals (e.g., copper, iron) from residual mineral ore. Prolonged suspension of small particles in the water column may bring them into contact with locally spawned pelagic fish eggs, including Atlantic cod, Gadus morhua . Newly fertilized cod embryos were exposed to suspended mine tailings particles up to 3.2 mg/L in flow‐through aquaria for a total of 21 d. Significantly more particles adhered to the surface of the chorion from the high treatment after 11‐d exposure, and dissolved Cu concentrations increased in the water (up to 0.36 ± 0.06 µg/L). There was no adverse effect on embryo mortality but an 8% elevation in larval mortality. There were no differences with treatment on timing of hatching, embryo and larva morphometrics, abnormalities, or cardiac activity. There was a treatment‐dependent up‐regulation of stress marker genes ( hspa8, cyp1c1 ) but no indication of metal‐induced activation of metallothionien ( mt gene transcription). Transcription markers for DNA and histone methyltransferases did show treatment‐related up‐regulation, indicative of altered methylation in larvae when developmental methylation patterns are determined, indicating some level of chronic toxicity that may have longer‐term effects.